2010
DOI: 10.1002/hep.23733
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing, microarray, and proteomic analyses reveal cellular and metabolic impact of hepatitis C virus infection in vitro†‡§

Abstract: Hepatitis C virus (HCV) is a major cause of liver disease but the full impact of HCV infection on the hepatocyte is poorly understood. RNA sequencing (RNA-Seq) is a novel method to analyze the full transcriptional activity of a cell or tissue, thus allowing new insight into the impact of HCV infection. We conducted the first full-genome RNA-Seq analysis in a host cell to analyze infected and noninfected cells, and compared this to microarray and proteomic analyses. The combined power of the triple approach rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 48 publications
4
73
1
Order By: Relevance
“…A breakthrough in HCV research was the discovery of an HCV strain, JFH1, capable of replicating efficiently and of producing viral particles in cultured cells (4)(5)(6). In this in vitro model of HCV infection, transcriptomic analyses revealed regulation of the expression of genes involved in apoptosis and cell cycle arrest (7)(8)(9)(10), while proteomic studies identified numerous perturbations in the metabolism of phospholipids and sphingomyelins that are predicted to play important roles in viral replication, assembly, and secretion (11). This suggests that important differences exist between the HCV-regulated transcriptome and proteome that may rely on the differential stability of proteins and/or on gene expression regulation at the mRNA translation level, the process by which proteins are synthesized from existing mRNAs.…”
mentioning
confidence: 99%
“…A breakthrough in HCV research was the discovery of an HCV strain, JFH1, capable of replicating efficiently and of producing viral particles in cultured cells (4)(5)(6). In this in vitro model of HCV infection, transcriptomic analyses revealed regulation of the expression of genes involved in apoptosis and cell cycle arrest (7)(8)(9)(10), while proteomic studies identified numerous perturbations in the metabolism of phospholipids and sphingomyelins that are predicted to play important roles in viral replication, assembly, and secretion (11). This suggests that important differences exist between the HCV-regulated transcriptome and proteome that may rely on the differential stability of proteins and/or on gene expression regulation at the mRNA translation level, the process by which proteins are synthesized from existing mRNAs.…”
mentioning
confidence: 99%
“…FASN is also upregulated in HCV-infected Huh7 cells (18). Accordingly, a significantly higher level of free fatty acid was detected in HCV-infected than in uninfected Huh 7.5 cells (40). Consequently, more lipid droplets were formed for HCV production (41).…”
Section: Discussionmentioning
confidence: 99%
“…95 In agreement with this, the expression of fatty acid synthase (FASN) and other genes related to the synthesis and transport of fatty acids is upregulated in infected cells. 87,88 Moreover, the inhibition of FASN activity blocks HCV RNA replication and production of infectious virus particles. 95,96 Finally, expression of genes regulating geranylgeranylation of cellular proteins important for HCV replication is also upregulated in HCV-containing cells.…”
Section: Hcv Proteinsmentioning
confidence: 99%
“…Indeed, recent studies based on transcriptome and proteomic analyses have demonstrated that expression of host genes involved in the biosynthesis, degradation and transport of intracellular lipids is profoundly altered upon infection. [86][87][88][89] The expression of SREBPs, which control transcription of genes required for cholesterol biosynthesis, 90 is stimulated both by HCV infection and It was demonstrated that NS proteins associate with cholesterol-rich lipid rafts and that depletion of cholesterol with statins selectively reduces HCV RNA replication. 104 However, statins are inhibitors of the mevalonate pathway, 99 which produces not only cholesterol, but also non-sterol isoprenoids, including geranylgeranyl and farnesyl.…”
Section: Role Of Lipid Metabolism In Hcv Rna Replicationmentioning
confidence: 99%